Crystal Structure and Active Site Engineering of a Halophilic γ-Carbonic Anhydrase - Vogler, Malvina; Karan, Ram; Renn, Dominik; Vancea, Alexandra; Vielberg, Marie-Theres; Grötzinger, Stefan W.; DasSarma, Priya; DasSarma, Shiladitya; Eppinger, Jörg; Groll, Michael; Rueping, Magnus (Frontiers in Microbiology, 2020)
Environments previously thought to be uninhabitable offer a tremendous wealth of unexplored microorganisms and enzymes. In this paper, we present the discovery and characterization of a novel γ-carbonic anhydrase (γ-CA) from the polyextreme Red Sea brine pool Discovery Deep (2141 m depth, 44.8 ˚C, 26.2% salt) by single-cell genome sequencing. The extensive analysis of the selected gene helps demonstrate the potential of this culture-independent method. The enzyme was expressed in the bioengineered haloarchaeon Halobacterium sp. NRC-1 and characterized by X-ray crystallography and mutagenesis. The 2.6 Å crystal structure of the protein shows a trimeric arrangement. Within the γ-CA, several possible structural determinants responsible for the enzyme’s salt stability could be highlighted. Moreover, the amino acid composition on the protein surface and the intra- and intermolecular interactions within the protein differ significantly from those of its close homologs. To gain further insights into the catalytic residues of the γ-CA enzyme, we created a library of variants around the active site residues and successfully improved the enzyme activity by 17-fold. As several γ-CAs have been reported without measurable activity, this provides further clues as to critical residues. Our study reveals insights into the halophilic γ-CA activity and its unique adaptations. The study of the polyextremophilic carbonic anhydrase provides a basis for outlining insights into strategies for salt adaptation, yielding enzymes with industrially valuable properties, and the underlying mechanisms of protein evolution.